1975
DOI: 10.1002/cpt1975173330
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of gastrointestinal effects of aspirin

Abstract: The effect of acetylsalicylic acid (aspirin) on the ultrastructure of gastric and jejunal mucosa was investigated in patients undergoing gastric surgery and in guinea pigs. The drug caused various degrees of damage to the surface mucous cells in both species perceptible as general signs of cytolysis in situ or as desquanmation. In patients pretreated with aspirin, an increase of secondary lysosomes was noted in the gastric parietal cells but not in the animals. In the intestinal epithelial cells of both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These results are in agree ment with previous studies reporting the defi ciency of mucin production and/or storage in gastric mucosa of animals or humans treated with aspirin and studied under fasting condi tions (3,9,12,14,33).…”
Section: Fasting Secretionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agree ment with previous studies reporting the defi ciency of mucin production and/or storage in gastric mucosa of animals or humans treated with aspirin and studied under fasting condi tions (3,9,12,14,33).…”
Section: Fasting Secretionsupporting
confidence: 93%
“…Histochemical studies of salicylateinduced lesions of gastric mucosa in rats (12) demonstrated a reduction in mucopolysaccha rides in both surface and deeply situated mucous-secreting cells. Aspirin-induced lesions of human and guinea pig gastric mucosa dis played various degrees of damage to the mu cous cells, consisting mostly of cytolysis and desquamation (33). Menguy and Masters (14) studied the effect of parenteral aspirin in rats and dogs and found inhibition of the rate of gastric mucus production; the reduction of hexosamine and A-fucose was observed in histochemically stained gastric mucosa sections.…”
Section: General Commentsmentioning
confidence: 99%
“…It will be of interest to correlate the functional changes of intestinal absorption noted in our study with possible structural alterations of intestinal epithelial cells. In one study, Hahn et al (1975) examined the effect of aspirin on the ultrastructure ofjejunal mucosa after administration of 3 g aspirin daily for three to five days. They found a marked increase of secondary lysosomes, probably representing autophagolysosomes, as well as an increase of multivesicular bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal inclusion bodies have been described in the apical cytoplasm of small intestinal epithelial cells in / 3 lipoprotein deficiency (6), coeliac disease (14), tropical sprue (12), infantile malnutrition (5), Crohn's disease (15), and after aspirin ingestion (9). It has been suggested that these inclusion bodies are autophagosomes, bacteria or dead epithelial cells ingested by their neighbours.…”
Section: Ae Acrodermatitis Enteropathicamentioning
confidence: 99%